Utilización de diferentes niveles de salvado de trigo (15% de almidón) en la alimentación de cuyes (Cavia porcellus) en la etapa reproductiva. - Pico Aguilar, Jhomayra Brigitt (2025)
This experimental research was carried out with the purpose of evaluating the productive and reproductive parameters. It will be developed within the seed project "Productive evaluation of minor species" in the animal production program of the Veterinary Medicine career of the Faculty of Agricultural Sciences of the Technical University of Babahoyo located at kilometer 1.5 of the Babahoyo - Montalvo Road in the province of Los Ríos. It will be carried out through three treatments versus a control treatment, each treatment will be made up of 4 treatments and 3 repetitions with 12 Experimental Units, which will be made up of 5 animal units with a total population of 60 animals in the entire research. The treatments were distributed under a Completely Randomized Design (CRD), where the experimental results obtained were subjected to an Analysis of Variance for differences (ANOVA), and Separation of Means according to Tukey at the significance levels of (P ≤ 0.05 and P ≤ 0.01), with the inclusion of wheat bran in the nutritional diets of the guinea pigs. Where the results were obtained with T0 a weight at the beginning of gestation was achieved 2151.96 (g), with T0 weight at the end of gestation 2511.96 (g), with T0 the gestation percentage 73.33 (%), with T0 the prolificacy percentage 66.67 (%), with T0 the number of born pups 3.33 (%), with T0 the number of weaned pups 3.33 (%), in mortality 0%, with T1 the weight of the pup at birth 264.17 (g), with T1 with the weight of the pup at weaning 308.33 (g), in T1 the live weight gain with 132.67 (g), in T3 the feed consumption 7.2 (g), in the Benefit/Cost ratio the best results were obtained in T0 with 1.7 sufficient reasons to be considered as a food within the production of guinea pigs in the tropics to improve productive parameters. The results offer relevant information to improve productive and reproductive parameters in the production of guinea pigs, contributing a diet to minimize feed costs.